Niger : Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Nonobservance of Performance Criteria, and Request for a New Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Niger. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper examines Niger's sixth review under the three-year arrangement under the Poverty Reduction and Growth Facility (PRGF). A successor PRGF-supported program would support the authorities' efforts to move toward meeting the Millennium Development Goals (MDGs) while preserving economic stability. Among the risks to the new program are adverse climatic shocks, higher food and international oil prices, and the insurgency in the North. IMF staff supports the requests for the waivers for nonobservance of two performance criteria, and the request for a new PRGF arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet